Recuperação do sorriso em crianças e adolescentes acometidos por fluorose dentária endêmica - Thalita Thyrza de Almeida Santa Rosa (2013)
This study aimed to describe and assess the physical and psychosocial impact of endemic dental fluorosis in children and adolescents before and after and restorative aesthetic treatment and develop and validate an instrument to verify self-perception of dental appearance. It is quasi-experimental study that had a reference population of children and adolescents who had dental fluorosis with aesthetic problems and receiving direct restorative dental treatment done by dentists linked to an intervention action. Questionnaires were administered on two occasions with an interval of 24 months (before and after dental treatment). The questionnaires were composed of questions concerning the physical and psychosocial impact of dental fluorosis (OHIP-14), self-perceived oral health (How would you rate your oral health?) and self-perceived dental appearance (six issues). The treatments were performed: microabrasion, direct resin composite veneers and combination of two techniques. Initially, descriptive analyzes were conducted. Was measured the prevalence, severity and extent of physical and psychosocial impact fluorosis from the OHIP-14. Comparisons between baseline and follow-up and between treatment techniques were carried out using the McNemar test, Wilcoxon and Mann-Whitney. In the process of validation of the Self-Perception Instrument Appearance Dental (IDAS), composed of six questions, was evaluated the internal consistency (Cronbach's alpha) and the adequacy of the data for factorial analysis (KMO test and Bartlett Sphericity). Construct validity was assessed using exploratory factor analysis. In the analysis of hypothesis, was sought to check the power of the scale to discriminate groups regarding traits that scale measures: Perception of appearance and psychological and social impact. For this, was defined groups with and without impact to areas as psychological discomfort, psychological disability and social assessed using the OHIP-14. The Mann- Whitney test was used to assess the frequency of items IDAS in groups with positive or negative self-perception of oral health. The follow-up of patients was performed between 2009 and 2013. After completion of restorative treatments, there was significant improvement in the prevalence, severity and extent of physical and psychosocial impact of fluorosis. Cronbach's alpha for the six items of the proposed instrument was 0,745. The correlation coefficients for each item full scale ranged from 0,22 to 0,68 . Factorial analysis revealed the presence of two constructs, which together explained 66,38% of the variance. The sample was adequate for factor analysis (KMO = 0,712). The good psychometric parameters found and a positive correlation with instrument widely used to measure physical and psychosocial impact of oral health (OHIP-14) refer to the possibility of wider use of IDAS in other studies. Keywords: Fluorosis, Dental, Endemic Diseases, OHIP-14, Self-Perception, Appearance, Validation, Children, Teens.